Cl− as a Chemical Fingerprint of Solute Transport in the Aquitard-Aquifer System of the North Jiangsu Coastal Plain, China. (9th November 2017) - Ge, Qin; Liang, Xing; Jin, Menggui; Li, Jing; Liu, Yan
Abstract : Detailed vertical profiles of Cl − in porewaters through the aquitard-aquifer system were used to yield solute transport mechanism and build a conceptual model regarding evolution processes and transport time of natural tracer migration in North Jiangsu coastal plain, China. One-dimensional vertical simulated models of Cl − profiles illustrate that diffusion appeared to be the dominant solute transport mechanism in the aquitard-aquifer system. A downward groundwater flow did not improve the fitness between simulated and measured values. Several simulated models were constructed and suggested that the evolution of the Cl − profiles is mainly ascribed to the introduction of seawater and freshwater of transgression-regression to the first confined aquifer and the upper boundary. Groundwater in the first confined aquifer recharged by the Late Pleistocene glacial meltwater (25–15 ka BP) was supported in response to the low Cl − concentrations. The shallow groundwater in the first confined aquifer and porewater with high salt were attributable to the Holocene seawater intrusion. These timeframes were also consistent favorably with the results of previous studies into the palaeohydrology of the study area.